Integrated culture of Haliotis asinina, donkey's ear abalone and halothuria scabra, sandfish in tanks a multi-trophic approach (IMTA) - Tupas-Bautista, Richelle (University of the Philippines Visayas, 2015)
Abalones were fed with Gracilaria seaweeds and their feces/pseudofeces served as feed for sandfish. Another group of sandfish juveniles were fed with Sargassum powder and another without feeding but dependent on the natural environment for food. The organic matter content was highest for abalone with 3 sandfish and different significantly with the monoculture of abalone and sandfish without feeding. The ammonia and nitrite content showed an increasing trend from Day 10 to Day 60 but in minimal amount or undetected with no significant difference among treatmennts, The positive mean daily growth and survival rates of abalone with 6 sandfish were significantly higher with the abalone monoculture but without significant difference with abalone having 3 and 9 sandfish. However, all sandfish exhibited a negative change in weight in all treatments with significant difference between 3 sandfish as compared with 6 and 9 sandfish co-cultured with abalone. A significant change in weight difference between sandfish with feeding and sandfish co-cultured with abalone was also obtained ; wheresa sandfish fed with Sargassum showed no significant difference with the two treatments. Proximate analysis of a healthy sandfish before the experiment showed a crude protein value of 22.11 + 1.29 which lowered significantly after the experiment for sandfish without feeding (10.28+ 0.43), sandfish fed with Sargassum (7.88+0.32) and sandfish with abalone (9.6+0.3). An increase in ash content for sandfish without feeding (96.25%), sandfish fed with sargassum (83.43%) and sandfish with abalone (92.75%) indicated weight loss equivalent. Hence, the sandfish were not feeding with good nutrient composition. A notable survival rate of treatment with 6 sandfish must be further investigated to compare growth when fed with combination of diets to include the abalone feces and pseudofeces when fed with artificial diets. Moreover,, further investigation is needed to check on the hydrogen sulfide content of the sand substrate and for an ideal culture area to increase water flow rate. Culturing abalone with bigger sizes of sandfish might also improve the latter's growth and survival rates using 6 snadfish as the standard stocking density.